2017
DOI: 10.1177/0300060517722696
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hamstring and patellar tendon grafts in anterior cruciate ligament reconstruction: A prospective randomized study

Abstract: ObjectiveThis prospective randomized study was performed to compare the outcomes of two operative methods of anterior cruciate ligament (ACL) reconstruction based on either bone–patellar tendon–bone (BTB) grafts or hamstring tendon (HT) grafts.MethodsAmong 100 patients, 96 completed the full follow-up period and were included in the final analysis (48 in the BTB group and 48 in the HT group). The patients were evaluated preoperatively and 1, 3, 6, and 12 months after ACL reconstruction. The Kujala score, Tegne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Results of this study were similar to the previous studies, where no difference was found between two grafts in terms of functional outcome 1314151631. Stańczak et al in their prospective study observed that type of graft had no effect on the functional outcome of ACL reconstruction 11. Return to sports was observed to be early and higher with BPTB graft as compared to STGPI graft.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results of this study were similar to the previous studies, where no difference was found between two grafts in terms of functional outcome 1314151631. Stańczak et al in their prospective study observed that type of graft had no effect on the functional outcome of ACL reconstruction 11. Return to sports was observed to be early and higher with BPTB graft as compared to STGPI graft.…”
Section: Discussionsupporting
confidence: 88%
“…The hamstring tendon graft does have its pros and cons such as its association with joint laxity,8 reduced hamstring strength,9 and higher graft rupture rate 10. However, most of the peer-reviewed articles showed satisfactory results with both the grafts 11121314151617. In the previous study, it was observed that doubled loop STG graft with preserved tibial insertion (STGPI) was superior to free double looped STG graft in terms of knee stability and functional outcome 18.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Stan'czak et al states that there is comparable improvement in patients undergoing ACLR with bone tendon patellar graft and Hamstring graft, with improvement in most sub scores of the KOOS scoring system and the Kujala score, After one year follow-up no statistical significance between the 2 groups. 25 In our study only Hamstring tendon grafts were used and showed improvement in all the subscales of KOOS after 1 year of follow up.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies without parameters for these demographics have shown comparable results in outcomes with each graft choice. 4,5,7,9 However, other studies have shown that in high school and…”
Section: See Related Article On Page 2279mentioning
confidence: 95%
“…2,3 However, a primary limitation of studies with large sample sizes that compare outcomes with different grafts for ACLR is their poor generalizability to specific patient populations. The clinical outcomes following ACLR with BPTB and HT autograft have been well reported at the mid-to long-term follow-up, [4][5][6][7] although further investigation of the application of these grafts in specific patient populations, particularly young athletes and female patients, is needed to determine their clinical efficacy in different contexts.…”
Section: See Related Article On Page 2279mentioning
confidence: 99%